دور الاعلام المدرسي في الالتزام التدابير الوقائية ضد فيروس كورونا دراسة ميدانية بمؤسسة الجودي بلقاسم - خيرة قويدري; جهاد لجواد; ناصر جلالي (My University, 2022)
The aim of this study is to reveal and identify the role of school media in respecting preventive measures against the corona virus from the point of view of Joudi belkacem high school students. In order to achieve the objectives of this study, the following questions were formulated. - What is the role of the school media in Algerian educational institutions from the Corona virus? - Does school media lead to respect for distance? - Does school media lead to a mask? The descriptive approach was used in this study, The study sample amounted to 26 male and female students at Joudi Belkacem high school, which were chosen randomly in the academic year 2020- 2021. We also used a questionnaire consisting of 24 items distributed on the two axes of school media and the Corona virus.